2018
DOI: 10.1016/j.eurpolymj.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Stored energy accompanying cyclic deformation of filled rubber

Abstract: International audienceThe hysteresis observed in the mechanical response of filled rubbers is classically assumed to be due to viscosity. In this study, a complete energy balance is carried out during cyclic deformation of a filled acrylonitrile-butadiene rubber. Results show that for the studied material, viscosity is not the preponderant contribution to the hysteresis loop: the mechanical energy brought to the material is not entirely dissipated into heat but a contrario is mainly used by the material to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…This suggested that at low protein filler loading, more strain energy applied during extension was recovered upon retraction compared to unfilled and highly filled rubber compounds. 55,56 Hysteresis decreased with repeat cycling and, after a few extension/retraction cycles, known as the conditioning period, the hysteresis reached a relatively constant value. There are many applications that require low hysteresis at elongations of several hundred to thousand percent, such as rubber bands, gloves, balloons, and threads/fibers for golf balls, among others.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that at low protein filler loading, more strain energy applied during extension was recovered upon retraction compared to unfilled and highly filled rubber compounds. 55,56 Hysteresis decreased with repeat cycling and, after a few extension/retraction cycles, known as the conditioning period, the hysteresis reached a relatively constant value. There are many applications that require low hysteresis at elongations of several hundred to thousand percent, such as rubber bands, gloves, balloons, and threads/fibers for golf balls, among others.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…52,53 In tire treads, low hysteresis is important to lowering rolling resistance. 55,56 Low protein filler loadings of 1-2 phr resulted in more energy storage, especially compared to ZnO filler, at increased extension/retraction cycles [- Figure 5(a)]. ZnO has high thermal conductivity and so can reduce heat build-up.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Else, it is necessary to distinguish the part of the mechanical energy converted into heat from the one stored by the material to change its microstructure. For that purpose, the ratio γ s e recently proposed by Le Cam and co‐workers() is used: γse=WstoredcycleWhystcycle, where Wstoredcycle=WhystcycleWintrinsiccycle.…”
Section: Thermodynamic Frameworkmentioning
confidence: 99%
“…The material stores part of the mechanical energy brought and releases it (or a part of it) with a different kinetics. ()…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation